SPEECH ETIQUETTE, NORMS AND CULTURE OF SPEECH (Eureka Journal of Humanities and Social Research, 2025)
The article is devoted to the basic concepts of speech etiquette, its norms and the role of speech culture in modern society. The functions of speech etiquette, the principles of correct speech behavior and the influence of cultural norms on the quality of communication are considered.
Keywords: Speech etiquette, culture of speech, etiquette, ethical norms of communication, linguistic behavior, norms of behavior, manner of communication, politeness, tactfulness, correctness, modesty, obligation, formulas of speech etiquette.